2003
DOI: 10.1038/sj.bjc.6600972
|View full text |Cite
|
Sign up to set email alerts
|

Associations of adult measures of childhood growth with breast cancer: findings from the British Women's Heart and Health Study

Abstract: Since the two components of adult height -leg length and trunk length -are poorly correlated with each other and appear to be influenced by different early life factors, examining their separate influence on breast cancer may provide additional insights into the mechanisms responsible for the positive association between adult height and breast cancer. In a cross-sectional study of 4286 women aged 60 -79 years, in whom there were 170 cases of breast cancer, we found total height, leg length and trunk length we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 39 publications
2
31
0
1
Order By: Relevance
“…It was therefore possible that IQ would only be related to one particular component of height. A study of height, leg length and trunk length in the British Women's Heart and Health Study found that height and its components were all positively associated with breast cancer (Lawlor et al, 2003). The IQ effect on offspring height survived adjustment for the social factors but not adjustment for parental height.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was therefore possible that IQ would only be related to one particular component of height. A study of height, leg length and trunk length in the British Women's Heart and Health Study found that height and its components were all positively associated with breast cancer (Lawlor et al, 2003). The IQ effect on offspring height survived adjustment for the social factors but not adjustment for parental height.…”
Section: Discussionmentioning
confidence: 99%
“…Women's social class was based on their own occupation (Gunnell et al, 2003). Deprivation category was derived from the home address.…”
Section: Offspring Variablesmentioning
confidence: 99%
“…Age was calculated from the date of birth and the date of entry to study. BMI was calculated from the height and weight measured by a nurse at the baseline medical examination (18). Data on physical activity levels (hours of physical activity in a typical week) and smoking (never, past, current 1-9, current 10-19 cigarettes/day, current 20-29 and current >29 cigarettes) were obtained from the self-completed baseline questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…This ongoing cohort study comprises 4,286 women aged 60 to 79 years at the baseline assessment undertaken between 1999 and 2001, who were randomly selected from 23 towns in Britain. Full details of the data collection have been published previously (17,18). The participants were flagged with the National Health Service Cancer Register for information on cancer registrations and deaths, and all deaths registered up to 31 January 2006 were included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation